2015
DOI: 10.1016/j.str.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A Native-like Intermediate Serves as a Branching Point between the Folding and Aggregation Pathways of the Mouse Prion Protein

Abstract: SUMMARY Transient folding intermediates and/or partially unfolded equilibrium states are thought to play a key role in the formation of protein aggregates. However, there is only indirect evidence linking accumulation of folding intermediates to aggregation, and the underlying mechanism remains to be elucidated. Here we show that a partially unfolded state of the prion protein accumulates both as a stable equilibrium state at acidic pH (A-state) and as a late folding intermediate. With a time resolution of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 54 publications
(83 reference statements)
4
40
0
1
Order By: Relevance
“…Such a structural perturbation also appears to have occurred in a molten globule-like kinetic intermediate that is also populated at equilibrium under highly acidic conditions, which has been implicated as a key precursor to oligomerization (68,69). Molecular dynamics studies on the prion protein (34,70) residues in the protein.…”
Section: Table 2 Identification Of the Slow Exchanging Residues Of Momentioning
confidence: 99%
“…Such a structural perturbation also appears to have occurred in a molten globule-like kinetic intermediate that is also populated at equilibrium under highly acidic conditions, which has been implicated as a key precursor to oligomerization (68,69). Molecular dynamics studies on the prion protein (34,70) residues in the protein.…”
Section: Table 2 Identification Of the Slow Exchanging Residues Of Momentioning
confidence: 99%
“…An interesting finding in the research on folding intermediates is the presence of the molten globule, wherein secondary structure elements are conserved in their native conformation, but the native side chain packing is perturbed in the tertiary structure . However, apart from molten globules, several intermediates can exist in the folding pathway of a protein with different amounts of secondary and tertiary structure . Direct detection of these higher energy intermediates is often impossible because they are unstable and transient .…”
Section: Introductionmentioning
confidence: 99%
“…Direct detection of these higher energy intermediates is often impossible because they are unstable and transient . Structural insights of higher intermediates can be obtained from NMR relaxation dispersion experiments, native state hydrogen exchange and thiol labeling experiments . Molecular dynamics (MD) simulations can also potentially hint towards the existence of higher energy intermediates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early efforts in the understanding of genetic prion disease found little evidence to support a change in the global stability as a means to explain enhanced misfolding in the disease associated variants [21]. Subsequent study then focused on the identification of folding intermediates using a variety of approaches that all showed that the C-terminal portion of the prion protein folded more rapidly [22,23]. Investigation into pre-oligomer structures also showed the presence of an acid-induced molten globule state where the C-terminal region remained folded but under physiologic conditions an equilibrium intermediate is not detected [24].…”
Section: Discussionmentioning
confidence: 99%